HUBUNGAN ANTARA KELEBIHAN BERAT BADAN DENGAN KEJADIAN OSTEOARTRITIS PADA LANSIA DI WILAYAH KERJA PUSKESMAS HANDAPHERANG KABUPATEN CIAMIS TAHUN 2018 - dini silva miranti; aap apipudin; ade fitriani (LPPM STIKes Muhammadiyah Ciamis, 2020)
Individually, at the age of 50 years there is a natural aging process. This can cause physical, mental, social, economic and psychological problems. At an advanced age, there is a decrease in the musculoskeletal system. The decline of the musculoskeletal system is characterized by the presence of pain in the joint area of one of osteoarthritis. Being overweight is one of the strongest modifiable risk factors for osteoarthritis. The method in this research is descriptive analytic by using cross sectional approach that is collecting data collected at one time simultaneously. Population in this research is all elderly in Working Area of Health Unit of Health Center Handherang of Ciamis Regency in 2017 6587 people. Sampling in this research by proportional random sampling is the sample size taken based on the proportion of each member of the population and obtained a sample of 99 people.The results showed that overweight of the elderly were overweight (58.6%), the osteoarthritis was mostly 54 (54.5%) and there was a significant relationship between being overweight and the incidence of osteoarthritis in the elderly because of the value of ?>? value (0.05> 0,000) and the value of chi square (?2) count> chi square (?2) table (34.643> 3,841).Suggestions are expected to maintain ideal body weight so as not to experience obesity, either by routine exercise and a balanced diet by avoiding fast food and high fat